Evaluation Of The Implementation Of Environmental Accounting Disclosures/ PSAK Number.32 At The Go Public Forestry Exploitation Company In Indonesia - Eksa Ridwansyah; Damayanti Damayanti (Politeknik Negeri Lampung, 2013)
In helping government to minimize the deforestation, Indonesian Institute of Accountants (IAI) has released the accounting standardÂ number 32 that gives standard for forestry companies in disclosing their activities that related to forest management. Therefore, the research aims is to evaluate the level of environmental disclosures of forestry companies that listed in Indonesia Stock Exchange. The data used is income statement from 2004 until 2007 and evaluated using qualitative descriptive. All of the information at income statement that related to environmental information then calculated as disclosure index. the disclosure index for all companies are between 0,58% and 0,8%.Â Keywords: disclosure index, forestry company, environmental information.Â